Systematic Literatur Review: Software Matematika Geogebra Sebagai Media Belajar Untuk Mengetahui Kemampuan Komputasi Peserta Didik - Lilis Suryani Nasution; Yahfizham Yahfizham (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
During the period of compulsory education in Indonesia, which is 12 years, the government requires mathematics as the main learning subject for extracts which will continue to have an impact on people’s lives. The level of ability in a field of science must be measured to obtain valid data for the development of education in Indonesia. The use of Geogebra Mathematics Software in schools in Indonesia is not surprising at this time, technological developments have made the use of Geogebra mathematics software commonplace. This research is a Systematic Literature Review, in this research the author analyzes and compares several articles obtained from the internet or digital databases, for example Semantic Scholar or Sprinter Link. The articles that have been found are then selected according to the title researched, so that several reference articles are obtained. The research results show that the use of Geogebra mathematics software in learning has a great influence on students’ computing abilities. Geogebra is a media with a visual, analytical and numerical approach that can be solved using algorithms that require computational capabilities to operate. There is empathy in computational thinking, namely algorithmic thinking problem solving, pattern recognition, and abstraction and generalization.